Prognostic value of reduced heart rate reserve during exercise in hypertrophic cardiomyopathy - Ciampi, Quirino (2021)
Background: Sympathetic dysfunction can be evaluated by heart rate reserve (HRR) with exercise test. Objectives: To determine the value of HRR in predicting outcome of patients with hypertrophic cardiomyopathy (HCM). Methods: We enrolled 917 HCM patients (age = 49 +/- 15 years, 516 men) assessed with exercise stress echocardiography (ESE) in 11 centres. ESE modality was semi-supine bicycle in 51 patients (6%), upright bicycle in 476 (52%), and treadmill in 390 (42%). During ESE, we assessed left ventricular outflow tract obstruction (LVOTO), stress-induced new regional wall motion abnormalities (RWMA), and HRR (peak/rest heart rate, HR). By selection, all patients completed the follow-up. Mortality was the predetermined outcome measure Results: During ESE, RWMA occurred in 22 patients (2.4%) and LVOTO (>= 50 mmHg) in 281 (30.4%). HRR was 1.90 +/- 0.40 (lowest quartile <= 1.61, highest quartile > 2.13). Higher resting heart rate (odds ratio 1.027, 95% CI: 1.018-1.036, p < 0.001), older age (odds ratio 1.021, 95% CI: 1.009-1.033, p < 0.001), lower exercise tolerance (mets, odds ratio 0.761, 95% CI: 0.708-0.817, p < 0.001) and resting LVOTO (odds ratio 1.504, 95% CI: 1.043-2.170, p = 0.029) predicted a reduced HRR. During a median follow-up of 89 months (interquartile range: 36-145 months), 90 all-cause deaths occurred. At multivariable analysis, lowest quartile HRR (Hazard ratio 2.354, 95% CI 1.116-4.968 p = 0.025) and RWMA (Hazard ratio 3.279, 95% CI 1.441-7.461 p = 0.004) independently predicted death, in addition to age (Hazard ratio 1.064, 95% CI 1.043-1.085 p < 0.001) and maximal wall thickness (Hazard ratio 1.081, 95% CI 1.037-1.128, p < 0.001). Conclusions: A blunted HRR during ESE predicts survival independently of RWMA in HCM patients.